Tha Viability of the John Murra Model in the Sama Valley - Yábar, Ben Yusef (2020)
The viability of the “vertical control” model John Murra is in force, but not in all its sense, nor in all the geographical spaces of the Andean world, but in the ethnic groups that met certain characteristics, such as being able to develop in axes where great coastal civilizations will not be found, as precisely happened with Sama in the current southern Peruvian extreme. However, recent discoveries have shown that not only was the vertical control exercised by the high plateau peoples, as was the case of the lupaqas over the coastal valleys, in this case Sama, but also other forms of complementarity coexisted such as retribution and exchange especially in the late period that corresponded to the Inca empire. Finally, it should be understood that there were also different types of control of ecological floors, both vertical, horizontal and other specific forms. The case is that this model cannot be generalized, as it was intended to be done between the 60s and 70s.